Perbandingan Stres yang Dirasakan Pasien Asma dan Pasien PPOK di RSUD Dr.Moewardi - Yunita, Amelia; Setijadi, Ana Rima; Widardo, . (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2014)
Asthma is a chronic inflammatory disorder of the airways with episodic symptom such as cough, shortness of breath, wheeze, and uplifted chest. Chronic Obstructive Pulmonary Disease (COPD) is a disease which is characterized by airflow limitation that is not fully revesible and associated with an abnormal inflammatory response of the lung to noxious particles or gases. This study aimed to compared the perceived stress between asthma patients and COPD patients. This analytic study was observational using cross-sectional approach. A sample of 60 study subjects was selective by purposive sampling from outpatient who visited Pulmonary Clinic, RSUD Dr. Moewardi and fulfill the intrinsic criteria. The data was collected by interview using a set of questioner. The data was analyzed using Chi Square test on SPSS 20 for windows. This study showed that asthma patients had a low stress level, which is 60%. While, in COPD patients had high stress level, which is 63.33%. (p=0.002, OR= 7.5) There is a statistically significant difference perceived stress between asthma patients and COPD patients. COPD patients had higher stress level compared to asthma patients.Â